CO2 anticorrosive agent, CO2-corrosion-resistant self-repairing cement slurry system and preparation method and application of CO2-corrosion-resistant self-repairing cement slurry system

By using CO2 anti-corrosion agent and CO2 corrosion-resistant self-repairing cement slurry system in CCUS projects, the corrosion problem of CO2 on cement cementing cement rings is solved, and intelligent repair of cement rings and safe sealing of CO2 is achieved.

CN119822667APending Publication Date: 2025-04-15CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311319924.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In CCUS project, the acidic medium CO2 causes serious corrosion to cement cement rings, casings and other underground tools, resulting in corrosion microcracks and microangle gaps of cement ring matrix, affecting the wellbore sealing and CO2 injection and sealing effect.

Method used

It provides a CO2 anti-corrosion agent and CO2 corrosion-resistant self-repair cement slurry system, which contains the CO2 anti-corrosion agent, including calcite, calcium carbonate whiskers and nano-silica. The cement slurry system is added with CO2 self-repair agent and CO2 anti-corrosion agent, which has a sensitive CO2 response and repair function.

Benefits of technology

In the CO2 environment, the cement slurry system can intelligently repair and fill microcracks and micro-angle gaps formed by CO2 corrosion, improve the compressive strength and repair strength of the cement ring, and ensure the safe sealing of CO2 and efficient oil discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004491387800000141
    Figure BDA0004491387800000141
  • Figure BDA0004491387800000151
    Figure BDA0004491387800000151
Patent Text Reader

Abstract

The invention provides a CO2 anticorrosive agent, an anti-CO2-corrosion self-repairing cement slurry system and a preparation method and application of the anti-CO2-corrosion self-repairing cement slurry system. The CO2 anticorrosive agent is prepared from the following components in parts by weight: 43 to 47 parts of calcite, 35 to 38 parts of calcium carbonate whisker and 15 to 22 parts of nano silicon dioxide. The CO2 corrosion resistant self-repairing cement paste system is prepared from the following components: 46 to 62 parts of G-grade oil well cement, 30 to 37 parts of superfine fly ash, 8 to 17 parts of phosphoaluminate cement, 4 to 6 parts of a CO2 self-repairing agent, 5 to 10 parts of a CO2 anticorrosive agent, 0.4 to 0.8 part of a fluid loss agent, 0.2 to 0.5 part of a dispersing agent, 0.05 to 0.10 part of a retarder, 0.05 to 0.10 part of a de-foaming agent and water. The CO2 corrosion resistant self-repairing cement slurry system not only has good CO2 corrosion resistance, but also has a sensitive CO2 response repairing function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of oil and gas exploration and development cementing engineering, and specifically relates to a CO2 corrosion inhibitor, a CO2 corrosion-resistant self-repairing cement slurry system, and a preparation method and application thereof. Background Art

[0002] CCUS (Carbon Capture, Utilization and Storage) is one of the key technologies to address climate change. Acidic medium CO2 gas poses a serious corrosion threat to cementing cement ring, casing and other downhole tools. After long-term CO2 corrosion damage, corrosion microcracks and micro-annuli occur in the cement ring matrix, the first interface and the second interface, resulting in failure of the annular seal of the injection and production wellbore, resulting in serious CO2 gas leakage, which not only poses a threat to the surrounding environment, but also seriously affects the CO2 injection and storage effect and oil recovery efficiency. Therefore, in order to fully ensure the safe storage of CO2 and efficient oil recovery, higher technical requirements are put forward for the sealing integrity and anti-CO2 corrosion characteristics of the cement ring of the injection and production wells in CCUS projects.

[0003] The CO2 corrosion-resistant self-repairing cement slurry system can intelligently repair and fill the cement annulus microcracks and micro-annular gaps formed by acidic CO2 corrosion in a responsive environment, giving the solidified cement stone the corrosion-resistant self-repairing property, so that the damaged cement annulus can be rebuilt and repaired and the long-term corrosion sealing integrity can be restored. CN1130060950B (Anti-crack self-repairing cement) discloses an anti-crack self-repairing cement, the components of which mainly include periclase, γ-C2S and dihydrate gypsum. The use of this anti-crack self-repairing cement to prepare concrete can effectively repair the number of early structural cracks in concrete in a water environment and reduce the width of later cracks.

[0004] CN116063050A (Active self-repairing cement slurry system responsive to oil and gas) discloses a cement slurry system with modified polyvinyl alcohol polymer as the key repair material. The cement stone formed after solidification has sensitive oil and gas response characteristics. When microcracks and micro-annular gaps appear in the wellbore cement ring, it can automatically block the oil and gas channel without manual intervention on the ground, restore the integrity of the cement ring and the interface bonding ability, and achieve the purpose of preventing casing annulus pressure. Although the above self-repairing system gives the cement stone / concrete microcrack self-repairing function, its response environment is oil and gas or water, that is, it is a self-repairing responsive material when it encounters hydrocarbons and water, and does not have the acidic medium CO2 response repair function. Summary of the invention

[0005] In order to solve the problems of annular air leakage and damage to wellbore integrity caused by micro-cracks and micro-annular gaps in the cement annulus corrosion of injection and production wells under CCUS conditions, the purpose of the present invention is to provide a CO2 corrosion inhibitor, a CO2 corrosion-resistant self-repairing cement slurry system and its preparation method and application. The CO2 corrosion-resistant self-repairing cement slurry system containing the CO2 corrosion inhibitor not only has good CO2 corrosion resistance, but also has a sensitive CO2 response repair function.

[0006] In order to achieve the above object, the present invention provides a CO2 corrosion inhibitor, which comprises 43-47 parts of calcite, 35-38 parts of calcium carbonate whiskers, and 15-22 parts of nano-silicon dioxide, calculated by weight.

[0007] According to a specific embodiment of the present invention, preferably, the calcite 80 mesh sieve pass rate is ≥95.0%; more preferably, the particle size distribution characteristics are as follows: <4μm: 23.71%; 4-10μm: 19.42%; 10-20μm: 25.60%; 20-40μm: 11.23%; 40-64μm: 9.75%; >64μm: 10.29%.

[0008] According to a specific embodiment of the present invention, preferably, the calcium carbonate whisker has a diameter of 1-2 μm, a fiber length of 20-30 μm, an aspect ratio of 20-30, and more preferably, a purity of ≥95.8%.

[0009] According to a specific embodiment of the present invention, preferably, the nano-silicon dioxide has a contact angle of 76°-83°, a particle size of 12-25 nm, and more preferably, a purity of ≥98.88%.

[0010] The present invention also provides a CO2 corrosion resistant self-repairing cement slurry system, which comprises, by weight:

[0011] 46-62 parts of G-grade oil well cement, 30-37 parts of ultrafine fly ash, 8-17 parts of phosphate aluminate cement, 4-6 parts of CO2 self-healing agent, 5-10 parts of the above-mentioned CO2 anti-corrosion agent, 0.4-0.8 parts of fluid loss reducer, 0.2-0.5 parts of dispersant, 0.05-0.10 parts of retarder, 0.05-0.10 parts of defoaming agent, and water; the ratio of the mass of the water to the sum of the masses of G-grade oil well cement, ultrafine fly ash, and phosphate aluminate cement is 0.38-1.30:1; wherein the CO2 self-healing agent has a core-shell structure; the core layer comprises a polymer obtained by polymerization of core layer monomers, and the core layer monomers include formaldehyde-urea prepolymer and crotonic acid; the shell layer comprises a polymer obtained by polymerization of shell layer monomers, and the shell layer monomers include acrylate monomers and cyclohexane lactam.

[0012] According to a specific embodiment of the present invention, preferably, based on the mass of the CO2 self-repairing agent as 100%, the composition of the CO2 self-repairing agent includes 30-34% formaldehyde-urea prepolymer, 25-29% crotonic acid, 23-26% acrylate monomer, and 11-22% cyclohexanelactam.

[0013] According to a specific embodiment of the present invention, preferably, the acrylic acid ester monomer includes one or a combination of two or more of butyl acrylate, ethyl acrylate, methyl methacrylate, methyl acrylate, and isooctyl acrylate.

[0014] According to a specific embodiment of the present invention, preferably, the method for preparing the CO2 self-repairing agent comprises the following steps:

[0015] (1) emulsion polymerization of the core layer monomer to obtain the core layer emulsion of the CO2 self-healing agent;

[0016] (2) The shell monomer is emulsion polymerized to prepare a shell layer on the surface of the core layer of the CO2 self-healing agent to obtain the CO2 self-healing agent.

[0017] According to a specific embodiment of the present invention, preferably, step (1) comprises the following steps:

[0018] (a) mixing the formaldehyde-urea prepolymer, crotonic acid, an emulsifier and water to obtain a core layer monomer solution;

[0019] (b) treating 25-35 wt % of the obtained core layer monomer solution with an initiator to obtain a core layer seed emulsion;

[0020] (c) adding the remaining core layer monomer solution and initiator to the obtained core layer seed emulsion for reaction to obtain the core layer emulsion of the CO2 self-healing agent.

[0021] According to a specific embodiment of the present invention, preferably, step (2) comprises the following steps:

[0022] (d) mixing the acrylic acid ester monomer, cyclohexanolactam, emulsifier and water to obtain a shell monomer solution;

[0023] (e) preparing a shell layer on the surface of the core layer of the CO2 self-healing agent by using the obtained shell layer monomer solution under the action of an initiator to obtain the CO2 self-healing agent.

[0024] According to a specific embodiment of the present invention, preferably, the method for preparing the formaldehyde-urea prepolymer comprises the following steps:

[0025] The raw material composition of the formaldehyde-urea prepolymer comprises urea and formaldehyde in a molar ratio of 1:1.1-1:1.4; 35-42% of the total amount of the urea raw material and polyacrylamide are mixed in water, the pH value is adjusted to 7-9 by triethanolamine, and the reaction is carried out at 50-65°C for 90-120 minutes; then 40-50% of the total amount of the urea raw material and a formaldehyde solution (the mass concentration is preferably 36%) are added, the pH value is adjusted to 4-6 by acetic acid, and the reaction is carried out for 120-150 minutes; finally, 8-25% of the total amount of the urea raw material is added, the pH value is adjusted to 4-6 by acetic acid, and the reaction is carried out at 65-70°C for 120-150 minutes to obtain the formaldehyde-urea prepolymer.

[0026] According to a specific embodiment of the present invention, preferably, the amount of polyacrylamide added is 3.5-6.2% of the total amount of urea raw material, and the molecular weight of the polyacrylamide is 3-5 million.

[0027] According to a specific embodiment of the present invention, preferably, in the method for preparing the CO2 self-repairing agent, the mass percentage concentration of the core layer monomer solution is 25-30% (calculated based on all solutes in the solution).

[0028] According to a specific embodiment of the present invention, preferably, in step (a), stirring is performed at 25000 r / min-28000 r / min for 15-20 min to obtain the core layer monomer solution.

[0029] According to a specific embodiment of the present invention, preferably, in step (a), the emulsifier includes a nonionic emulsifier, more preferably a mixture of dodecyl to octadecyl alcohol polyoxyethylene ether and octylphenol polyoxyethylene ether, further preferably a mixture of dodecyl to octadecyl alcohol polyoxyethylene ether and octylphenol polyoxyethylene ether in a mass ratio of 1:3.

[0030] According to a specific embodiment of the present invention, preferably, in step (a), the amount of the emulsifier added is 3.2-4.5% of the mass of the core layer monomer.

[0031] According to a specific embodiment of the present invention, preferably, in step (b), the amount of initiator added is 0.8-1.2% of the mass of the obtained core layer monomer solution of 25-35 wt%.

[0032] According to a specific embodiment of the present invention, preferably, in step (c), the amount of initiator added is 0.8-1.2% of the mass of the remaining core layer monomer solution.

[0033] According to a specific embodiment of the present invention, preferably, in step (b), the reaction temperature is 55-65°C.

[0034] According to a specific embodiment of the present invention, preferably, in step (c), at 65-70° C., the remaining core layer monomer solution and initiator are added dropwise to the core layer seed emulsion within 50-70 minutes, and the reaction is carried out for 6-8 hours.

[0035] According to a specific embodiment of the present invention, preferably, in step (b) or step (c), the initiator comprises azobisisobutyronitrile and ammonium persulfate, and more preferably, the initiator is added in the form of a composite solution of azobisisobutyronitrile and ammonium persulfate in a mass ratio of 1:1 and a mass concentration of 20-35%.

[0036] According to a specific embodiment of the present invention, preferably, in the method for preparing the CO2 self-healing agent, the mass percentage concentration of the shell monomer solution is 20-25% (calculated based on all solutes in the solution).

[0037] According to a specific embodiment of the present invention, preferably, in step (d), stirring is performed at 25000 r / min-28000 r / min for 15-20 min to obtain the shell layer monomer solution.

[0038] According to a specific embodiment of the present invention, preferably, in step (e), the amount of initiator added is 0.8-1.0% of the mass of the shell layer monomer solution.

[0039] According to a specific embodiment of the present invention, preferably, in step (e), at 85-90° C., the shell layer monomer solution and initiator are added dropwise to the core layer emulsion within 120-140 min, and the reaction is carried out for 10-12 h.

[0040] According to a specific embodiment of the present invention, preferably, in step (d), the emulsifier comprises nonylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate and sodium p-styrene sulfonate, more preferably a mixture of nonylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate and sodium p-styrene sulfonate in a mass ratio of 2:1:3.

[0041] According to a specific embodiment of the present invention, preferably, in step (d), the amount of the emulsifier added is 3.8-4.9% of the mass of the shell monomer.

[0042] According to a specific embodiment of the present invention, preferably, in step (e), the initiator comprises azobisisobutyronitrile and ammonium persulfate, and more preferably, the initiator is added in a composite solution of azobisisobutyronitrile and ammonium persulfate in a mass ratio of 1:1 and a mass concentration of 20-25% (calculated based on all solutes in the solution).

[0043] According to a specific embodiment of the present invention, the preparation method of the above-mentioned CO2 self-repairing agent comprises the following specific steps:

[0044] (1) Preparation of core layer CO2 responsive monomer solution:

[0045] Weigh formaldehyde-urea prepolymer, crotonic acid and emulsifier in proportion and dissolve them in water to prepare a solution with a mass percentage concentration of 25-30%, use a high-speed stirrer to mechanically stir the core layer monomer mixture for 15-20 minutes to obtain a core layer CO2 responsive monomer solution, and the stirring speed is 25000r / min-28000r / min;

[0046] The specific synthesis steps of the formaldehyde-urea prepolymer are as follows: the molar ratio of urea to formaldehyde is controlled to be 1:1.1-1:1.4. Weigh 35-42% of the total amount of urea and polyacrylamide, adjust the pH value of the system to 7-9 with triethanolamine solution, heat to 50-65°C and stir to react for 90-120 minutes; then add the remaining 40-50% urea and a formaldehyde solution with a specified mass concentration of 36%, adjust the pH value of the system to 4-6 with acetic acid solution, and stir to react for 120-150 minutes; finally weigh 8-25% of the total amount of urea, adjust the pH value to 4-6 with acetic acid solution, heat to 65-70°C and stir to react for 120-150 minutes to obtain the formaldehyde-urea prepolymer. The amount of polyacrylamide added is 3.5-6.2% of the total amount of urea, and its molecular weight is 3-5 million;

[0047] (2) Preparation of shell temperature responsive softening functional monomer solution:

[0048] Weighing acrylate monomers, cyclohexanolactam and emulsifiers in proportion and dissolving them in water to prepare a solution with a mass percentage concentration of 20-25%, using a high-speed stirrer to mechanically stir the shell monomer mixture for 15-20 minutes to obtain a shell temperature-responsive softening functional monomer solution, and the stirring speed is 25000r / min-28000r / min;

[0049] (3) Preparation of nuclear layer seed emulsion:

[0050] Weigh one-fourth of the core layer CO2 responsive monomer solution prepared in step (1) and add it to a five-necked flask equipped with a condenser, a stirrer, and a thermometer. Heat the solution to 55°C in a water bath and keep the temperature constant for 30 minutes. Add 0.8% of the initiator by weight of one-fourth of the core layer CO2 responsive monomer solution. When the solution shows a slight blue glow and the reflux disappears, the core layer seed emulsion is obtained.

[0051] (4) Preparation of CO2 self-healing agent core layer:

[0052] Weigh the remaining three quarters of the core layer CO2 responsive monomer solution in step (1) and 0.8% of the total mass of the three quarters of the monomer solution initiator, place them in constant pressure dropping funnel A and constant pressure dropping funnel B respectively, and install them on the five-necked flask in step (3), introduce nitrogen to deoxygenate for 15 minutes, heat the water bath to 65°C and keep the temperature constant for 30 minutes, open the constant pressure dropping funnel A and the constant pressure dropping funnel B, control the addition to be completed within 50 minutes, and continue the reaction for 6.0 hours, thus completing the preparation of the core layer of the CO2 self-healing agent;

[0053] (5) Preparation of CO2 self-healing agent shell:

[0054] The shell temperature responsive softening functional monomer solution in step (2) and 0.8% of the initiator by weight of the total solution are placed in constant pressure dropping funnel C and constant pressure dropping funnel D respectively and installed on the five-necked flask in step (4). Heat the water bath to 90°C and keep the temperature constant for 30 minutes. Open the constant pressure dropping funnel C and the constant pressure dropping funnel D. After the addition is completed within 120 minutes, continue the reaction for 12.0 hours. After cooling to room temperature, the CO2 self-healing agent is obtained.

[0055] According to a specific embodiment of the present invention, preferably, the G-grade oil well cement includes one or a combination of two or more of Jiahua G-grade oil well cement, Yaobei G-grade oil well cement, Jiulianshan G-grade oil well cement, Gezhouba G-grade oil well cement, Mengcheng G-grade oil well cement and Aksu G-grade oil well cement.

[0056] According to a specific embodiment of the present invention, preferably, the silicon content in the ultrafine fly ash is ≥96.0%, the silicon ratio value SM is between 1.8-3.2, and the passing rate of 1345 mesh sieve is ≥95.0%.

[0057] The present invention also provides a method for preparing the above-mentioned CO2 corrosion resistant self-repairing cement slurry system, which comprises the following steps:

[0058] The CO2 self-repairing agent, defoaming agent and water are mixed to obtain a mixed solution; Class G oil well cement, ultrafine fly ash, phosphate aluminate cement, CO2 anti-corrosion agent, fluid loss reducer, dispersant and retarder are mixed into a solid phase mixture, and then mixed with the obtained mixed solution to obtain the CO2 corrosion resistant self-repairing cement slurry system.

[0059] The present invention also provides the use of the CO2 corrosion resistant self-repairing cement slurry system as oil well cement.

[0060] The CO2 corrosion-resistant self-repairing cement slurry system of the present invention can intelligently repair and fill the cement annulus microcracks and micro-annular gaps formed by acidic CO2 corrosion in a CO2 response environment, giving the solidified cement stone anti-corrosion self-repairing properties, so that the damaged cement annulus can be rebuilt and repaired and the long-term corrosion sealing integrity can be restored, thus ensuring the safe storage of CO2 and high-efficiency oil recovery. The present invention has the following significant advantages:

[0061] 1. The CO2 corrosion-resistant self-repairing cement slurry system of the present invention has good CO2 response characteristics. It has rapid acidic medium response characteristics in a CO2 environment, forming a high-strength three-dimensional solidified material, which can give the cement sheath good compressive strength and repair strength;

[0062] 2. The cured body of the CO2 corrosion resistant self-repairing cement slurry system of the present invention has good flexibility. It has a fast temperature response characteristic in a CO2 environment and can form a tough polymer cross-linked substance inside the matrix;

[0063] 3. The CO2 corrosion resistant self-repairing cement slurry system of the present invention has good CO2 corrosion resistance and self-repairing properties. Compared with conventional cement paste and other anti-corrosion systems on the market, the cement paste formed by this product, under the conditions of total pressure of 35MPa\CO2 partial pressure of 30MPa, after 90 days of CO2 corrosion curing, the compressive strength stability can be enhanced by 93.73%, and the permeability recovery rate can be enhanced by 90.05%. DETAILED DESCRIPTION

[0064] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0065] The fluid loss reducer used below is the medium and low temperature polyethanol water-loss reducer (G309) produced by Henan Weihui Chemical Co., Ltd.; the dispersant is the aldehyde-ketone condensation product dispersant (USZ) produced by Henan Weihui Chemical Co., Ltd.; the retarder is the gluconate and low molecular weight organic acid compound retarder (GH-8) produced by Henan Weihui Chemical Co., Ltd.; the defoamer is the silicone oil defoamer (D50) produced by Tianjin PetroChina Boxing; the ultrafine fly ash was purchased from Shijiazhuang Zhengyu New Materials Technology Co., Ltd., and the phosphate aluminate cement was purchased from Sichuan Jiahua Enterprise (Group) Co., Ltd.

[0066] The CO2 anticorrosive agent is composed of 43-47 parts of calcite, 35-38 parts of calcium carbonate whiskers, and 15-22 parts of nano-silicon dioxide, wherein the passing rate of calcite on an 80-mesh screen is ≥95.0%, and the particle size distribution characteristics are as follows: <4μm: 23.71%; 4-10μm: 19.42%; 10-20μm: 25.60%; 20-40μm: 11.23%; 40-64μm: 9.75%; >64μm: 10.29%. Among them, the purity of calcium carbonate whiskers is ≥95.8%, the diameter range is 1-2μm, the fiber length range is 20-30μm, and the aspect ratio is 20-30. Among them, the purity of nano-silicon dioxide is ≥98.88%, the contact angle range is 76°-83°, and the particle size range is 12-25nm.

[0067] Preparation Example 1

[0068] This preparation example provides a formaldehyde-urea prepolymer, which is prepared by the following steps:

[0069] The molar ratio of urea to formaldehyde is controlled to be 1:1.2. Weigh 55.5g of urea and 6.0g of polyacrylamide with a molecular weight of 5 million and dissolve them in 100g of water. Use triethanolamine to adjust the pH value to 7, transfer to a 500mL three-necked flask, start the stirrer and heat to 55°C for stirring and reaction for 100min; then add 60g of urea and 249.75g of 36% mass concentration formaldehyde solution, use acetic acid solution to adjust the pH value of the system to 4, stir and react for 120min; finally, add 34.5g of urea, use acetic acid solution to adjust the pH value to 4, heat to 65°C and stir and react for 130min to obtain formaldehyde-urea prepolymer.

[0070] Preparation Example 2

[0071] This preparation example provides a formaldehyde-urea prepolymer comparative sample, which is prepared by the following steps:

[0072] The molar ratio of urea to formaldehyde is controlled to be 1:1.2. Weigh 55.5g of urea and 6.0g of polyacrylamide with a molecular weight of 5 million and dissolve them in 100g of water. Use sodium hydroxide to adjust the pH value to 7, transfer to a 500mL three-necked flask, start the stirrer and heat to 55°C for stirring and reaction for 100min; then add 60g of urea and 249.75g of 36% mass concentration formaldehyde solution, use acetic acid solution to adjust the system pH value to 4, stir and react for 120min; finally, add 34.5g of urea, use acetic acid solution to adjust the pH value to 4, heat to 65°C and stir and react for 130min to obtain a formaldehyde-urea prepolymer comparison sample. After the comparison sample is discharged, it is allowed to stand for 3.0 hours and directly stratified, and cannot be directly used later.

[0073] Preparation Example 3

[0074] This preparation example provides a CO2 self-repairing agent, which is prepared by the following steps:

[0075] (1) Preparation of core layer CO2 responsive monomer solution:

[0076] Weigh 30 g of formaldehyde-urea prepolymer (the product obtained in Preparation Example 1, the same below), 25 g of crotonic acid, 0.44 g of dodecyl alcohol polyoxyethylene ether, and 1.32 g of octylphenol polyoxyethylene ether and dissolve them in 165 g of water, adjust the stirrer speed to 26000 r / min, and stir the mixture at high speed for 15 min to obtain a core layer CO2 responsive monomer solution;

[0077] (2) Preparation of shell temperature responsive softening functional monomer solution:

[0078] Weigh 23 g of methyl methacrylate, 22 g of cyclohexane lactam, 0.70 g of nonylphenol polyoxyethylene ether, 0.35 g of sodium dodecylbenzene sulfonate, and 1.04 g of sodium p-styrene sulfonate and dissolve them in 220 g of water. Adjust the stirrer speed to 26000 r / min and stir the mixture at high speed for 15 min to obtain a shell temperature responsive softening functional monomer solution.

[0079] (3) Preparation of nuclear layer seed emulsion:

[0080] Weigh 55.44 g of the core layer CO2 responsive monomer solution and add it to a five-necked flask equipped with a condenser, a stirrer, and a thermometer. Heat the water bath to 55°C and keep the temperature constant for 30 min. Add 2.22 g of azobisisobutyronitrile and ammonium persulfate compound (mass ratio is 1:1) initiator solution (mass concentration is 20%). When the solution shows a slight blue glow and the reflux disappears, the core layer seed emulsion is obtained.

[0081] (4) Preparation of CO2 self-healing agent core layer:

[0082] Weigh 166.32g of the core layer CO2 responsive monomer solution and 6.65g of the initiator solution (mass concentration of 20%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1), place them in constant pressure dropping funnel A and constant pressure dropping funnel B respectively and install them on the five-necked flask in step (3), introduce nitrogen to deoxygenate for 15min, heat the water bath to 65°C and keep the temperature constant for 30min, open constant pressure dropping funnel A and constant pressure dropping funnel B, control the addition to be completed within 50min, and continue the reaction for 6.0h, thus completing the preparation of the CO2 self-healing agent core layer;

[0083] (5) Preparation of CO2 self-healing agent shell:

[0084] Weigh 267.09g of shell temperature responsive softening functional monomer solution and 6.65g of azobisisobutyronitrile and ammonium persulfate composite initiator (mass ratio of 1:1) solution (mass concentration of 20%) and place them in constant pressure dropping funnel C and constant pressure dropping funnel D respectively and install them on the five-necked flask in step (4), heat the water bath to 90°C and keep the temperature constant for 30min, open the constant pressure dropping funnel C and the constant pressure dropping funnel D, control the addition to be completed within 120min, and continue the reaction for 12.0h. After cooling to room temperature, CO2 self-healing agent A is obtained.

[0085] Preparation Example 4

[0086] This preparation example provides a CO2 self-repairing agent, which is prepared by the following steps:

[0087] (1) Preparation of core layer CO2 responsive monomer solution:

[0088] Weigh 34 g of formaldehyde-urea prepolymer, 29 g of crotonic acid, 0.71 g of tridecaned fatty alcohol polyoxyethylene ether, and 2.13 g of octylphenol polyoxyethylene ether and dissolve them in 147 g of water. Adjust the stirrer speed to 28000 r / min and stir the mixture at high speed for 20 min to obtain a core layer CO2 responsive monomer solution.

[0089] (2) Preparation of shell temperature responsive softening functional monomer solution:

[0090] Weigh 26 g of methyl methacrylate, 11 g of cyclohexane lactam, 0.60 g of nonylphenol polyoxyethylene ether, 0.30 g of sodium dodecylbenzene sulfonate, and 0.90 g of sodium p-styrene sulfonate and dissolve them in 111 g of water. Adjust the stirrer speed to 28000 r / min and stir the mixture at high speed for 15 min to obtain a shell temperature responsive softening functional monomer solution.

[0091] (3) Preparation of nuclear layer seed emulsion:

[0092] Weigh 53.21g of the core layer CO2 responsive monomer solution and add it to a five-necked flask equipped with a condenser, a stirrer, and a thermometer. Heat it to 60°C in a water bath and keep it at this temperature for 30min. Add 2.13g of an initiator solution (mass concentration of 22%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1). When the solution shows a slight blue glow and the reflux disappears, the core layer seed emulsion is obtained.

[0093] (4) Preparation of CO2 self-healing agent core layer:

[0094] Weigh 159.63g of the core layer CO2 responsive monomer solution and 6.39g of the initiator solution (mass concentration of 22%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1), place them in constant pressure dropping funnel A and constant pressure dropping funnel B respectively and install them on the five-necked flask in step (3), introduce nitrogen to deoxygenate for 15min, heat the water bath to 65°C and keep the temperature constant for 30min, open constant pressure dropping funnel A and constant pressure dropping funnel B, control the addition to be completed within 60min, and continue the reaction for 7.0h, thus completing the preparation of the CO2 self-healing agent core layer;

[0095] (5) Preparation of CO2 self-healing agent shell:

[0096] Weigh 111.0 g of shell temperature responsive softening functional monomer solution and 4.44 g of azobisisobutyronitrile and ammonium persulfate composite (mass ratio of 1:1) initiator solution (mass concentration of 22%) and place them in constant pressure dropping funnel C and constant pressure dropping funnel D respectively and install them on the five-necked flask in step (4). Heat the water bath to 85°C and keep the temperature constant for 30 minutes. Open the constant pressure dropping funnel C and the constant pressure dropping funnel D. After the addition is completed within 130 minutes, continue the reaction for 11.0 hours. After cooling to room temperature, CO2 self-healing agent B is obtained.

[0097] Preparation Example 5

[0098] This preparation example provides a CO2 self-healing agent comparison sample, which is prepared by the following steps:

[0099] (1) Preparation of core layer CO2 responsive monomer solution:

[0100] Weigh 30 g of formaldehyde-urea prepolymer (the product obtained in Preparation Example 1, the same below), 25 g of acrylic acid, 0.44 g of dodecyl alcohol polyoxyethylene ether, and 1.32 g of octylphenol polyoxyethylene ether and dissolve them in 165 g of water, adjust the stirrer speed to 26000 r / min, and stir the mixture at high speed for 15 min to obtain a core layer CO2 responsive monomer solution;

[0101] (2) Preparation of shell temperature responsive softening functional monomer solution:

[0102] Weigh 23 g of methyl methacrylate, 22 g of cyclohexane lactam, 0.70 g of nonylphenol polyoxyethylene ether, 0.35 g of sodium dodecylbenzene sulfonate, and 1.04 g of sodium p-styrene sulfonate and dissolve them in 220 g of water. Adjust the stirrer speed to 26000 r / min and stir the mixture at high speed for 15 min to obtain a shell temperature responsive softening functional monomer solution.

[0103] (3) Preparation of nuclear layer seed emulsion:

[0104] Weigh 55.44 g of the core layer CO2 responsive monomer solution and add it to a five-necked flask equipped with a condenser, a stirrer, and a thermometer. Heat the water bath to 55°C and keep the temperature constant for 30 min. Add 2.22 g of azobisisobutyronitrile and ammonium persulfate compound (mass ratio is 1:1) initiator solution (mass concentration is 20%). When the solution shows a slight blue glow and the reflux disappears, the core layer seed emulsion is obtained.

[0105] (4) Preparation of CO2 self-healing agent core layer:

[0106] Weigh 166.32g of the core layer CO2 responsive monomer solution and 6.65g of the initiator solution (mass concentration of 20%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1), place them in constant pressure dropping funnel A and constant pressure dropping funnel B respectively and install them on the five-necked flask in step (3), introduce nitrogen to deoxygenate for 15min, heat the water bath to 65°C and keep the temperature constant for 30min, open constant pressure dropping funnel A and constant pressure dropping funnel B, control the addition to be completed within 50min, and continue the reaction for 6.0h, thus completing the preparation of the CO2 self-healing agent core layer;

[0107] (5) Preparation of CO2 self-healing agent shell:

[0108] Weigh 267.09g of shell temperature responsive softening functional monomer solution and 6.65g of azobisisobutyronitrile and ammonium persulfate composite initiator (mass ratio of 1:1) solution (mass concentration of 20%) and place them in constant pressure dropping funnel C and constant pressure dropping funnel D respectively and install them on the five-necked flask in step (4). Heat the water bath to 90°C and keep the temperature constant for 30 minutes. Open the constant pressure dropping funnel C and the constant pressure dropping funnel D. After the addition is completed within 120 minutes, continue the reaction for 12.0 hours. After cooling to room temperature, the CO2 self-healing agent comparison sample C is obtained.

[0109] Preparation Example 6

[0110] This preparation example provides a CO2 self-healing agent comparison sample, which is prepared by the following steps:

[0111] (1) Preparation of core layer CO2 responsive monomer solution:

[0112] Weigh 34 g of formaldehyde-urea prepolymer, 29 g of crotonic acid, 0.91 g of heptathalloyl polyoxyethylene ether, and 0.91 g of octylphenol polyoxyethylene ether and dissolve them in 147 g of water. Adjust the stirrer speed to 28000 r / min and stir the mixture at high speed for 20 min to obtain a core layer CO2 responsive monomer solution.

[0113] (2) Preparation of shell temperature responsive softening functional monomer solution:

[0114] Weigh 26 g of methyl methacrylate, 11 g of cyclohexanolactam, 0.43 g of octylphenol polyoxyethylene ether, 0.43 g of sodium dodecyl sulfate, and 0.43 g of sodium p-styrene sulfonate and dissolve them in 111 g of water. Adjust the stirrer speed to 28000 r / min and stir the mixture at high speed for 15 min to obtain a shell temperature responsive softening functional monomer solution.

[0115] (3) Preparation of nuclear layer seed emulsion:

[0116] Weigh 53.21g of the core layer CO2 responsive monomer solution and add it to a five-necked flask equipped with a condenser, a stirrer, and a thermometer. Heat it to 60°C in a water bath and keep it at this temperature for 30min. Add 2.13g of an initiator solution (mass concentration of 22%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1). When the solution shows a slight blue glow and the reflux disappears, the core layer seed emulsion is obtained.

[0117] (4) Preparation of CO2 self-healing agent core layer:

[0118] Weigh 159.63g of the core layer CO2 responsive monomer solution and 6.39g of the initiator solution (mass concentration of 22%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1), place them in constant pressure dropping funnel A and constant pressure dropping funnel B respectively and install them on the five-necked flask in step (3), introduce nitrogen to deoxygenate for 15min, heat the water bath to 65°C and keep the temperature constant for 30min, open constant pressure dropping funnel A and constant pressure dropping funnel B, control the addition to be completed within 60min, and continue the reaction for 7.0h, thus completing the preparation of the CO2 self-healing agent core layer;

[0119] (5) Preparation of CO2 self-healing agent shell:

[0120] Weigh 111.0g of shell temperature responsive softening functional monomer solution and 4.44g of azobisisobutyronitrile and ammonium persulfate compound (mass ratio of 1:1) initiator solution (mass concentration of 22%) and place them in constant pressure dropping funnel C and constant pressure dropping funnel D respectively and install them on the five-necked flask in step (4), heat the water bath to 85°C and keep the temperature constant for 30min, open constant pressure dropping funnel C and constant pressure dropping funnel D, control the reaction to continue for 11.0h after the addition is completed within 130min, and cool to room temperature to obtain CO2 self-healing agent comparison sample D. This sample has poor stability and is directly stratified. It cannot be directly applied to cement slurry, and there is no need to test its anti-CO2 corrosion performance and self-healing performance.

[0121] Preparation Example 7

[0122] This preparation example provides a CO2 self-healing agent comparison sample, which is prepared by the following steps:

[0123] (1) Preparation of core layer CO2 responsive monomer solution:

[0124] Weigh 34 g of formaldehyde-urea prepolymer, 29 g of crotonic acid, 0.71 g of tridecaned fatty alcohol polyoxyethylene ether, and 2.13 g of octylphenol polyoxyethylene ether and dissolve them in 147 g of water. Adjust the stirrer speed to 21000 r / min and stir the mixture at high speed for 20 min to obtain a core layer CO2 responsive monomer solution.

[0125] (2) Preparation of shell temperature responsive softening functional monomer solution:

[0126] Weigh 26 g of methyl methacrylate, 11 g of cyclohexane lactam, 0.60 g of nonylphenol polyoxyethylene ether, 0.30 g of sodium dodecylbenzene sulfonate, and 0.90 g of sodium p-styrene sulfonate and dissolve them in 111 g of water. Adjust the stirrer speed to 21000 r / min and stir the mixture at high speed for 15 min to obtain a shell temperature responsive softening functional monomer solution.

[0127] (3) Preparation of nuclear layer seed emulsion:

[0128] Weigh 53.21g of the core layer CO2 responsive monomer solution and add it to a five-necked flask equipped with a condenser, a stirrer, and a thermometer. Heat it to 60°C in a water bath and keep it at this temperature for 30min. Add 2.13g of an initiator solution (mass concentration of 22%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1). When the solution shows a slight blue glow and the reflux disappears, the core layer seed emulsion is obtained.

[0129] (4) Preparation of CO2 self-healing agent core layer:

[0130] Weigh 159.63g of the core layer CO2 responsive monomer solution and 6.39g of the initiator solution (mass concentration of 22%) prepared by mixing azobisisobutyronitrile and ammonium persulfate (mass ratio of 1:1), place them in constant pressure dropping funnel A and constant pressure dropping funnel B respectively and install them on the five-necked flask in step (3), introduce nitrogen to deoxygenate for 15min, heat the water bath to 65°C and keep the temperature constant for 30min, open constant pressure dropping funnel A and constant pressure dropping funnel B, control the addition to be completed within 60min, and continue the reaction for 7.0h, thus completing the preparation of the CO2 self-healing agent core layer;

[0131] (5) Preparation of CO2 self-healing agent shell:

[0132] Weigh 111.0g of shell temperature responsive softening functional monomer solution and 4.44g of azobisisobutyronitrile and ammonium persulfate compound (mass ratio of 1:1) initiator solution (mass concentration of 22%) and place them in constant pressure dropping funnel C and constant pressure dropping funnel D respectively and install them on the five-necked flask in step (4), heat the water bath to 85°C and keep the temperature constant for 30min, open constant pressure dropping funnel C and constant pressure dropping funnel D, control the addition to be completed within 130min and continue the reaction for 11.0h, and cool to room temperature to obtain CO2 self-healing agent comparison sample E. After the sample was discharged and allowed to stand for 2 hours, it was directly stratified, which made it impossible to directly apply it to cement slurry, so there was no need to test its CO2 corrosion resistance and self-healing performance.

[0133] Preparation Example 8

[0134] This preparation example provides a CO2 anticorrosive agent, which is prepared by the following steps:

[0135] Weigh 215.0 g of calcite, 175.0 g of calcium carbonate whiskers and 110.0 g of nano-silicon dioxide, place them in a 1000 ml closed mixing tank, and continuously fill with 0.30 MPa nitrogen for 30 min to ensure that the powder materials are fully mixed, thereby obtaining CO2 corrosion inhibitor A.

[0136] Preparation Example 9

[0137] This preparation example provides a CO2 anticorrosive comparative sample, which is prepared by the following steps:

[0138] Weigh 215.0g of calcium oxide, 175.0g of calcium sulfate whiskers and 110.0g of nano-silicon dioxide, place them in a 1000ML closed mixing tank, and continuously fill with 0.30MPa nitrogen for 30min to ensure that the powder materials are fully mixed, thereby obtaining CO2 corrosion inhibitor comparison sample B.

[0139] Example 1

[0140] This embodiment provides a CO2 corrosion resistant self-repairing cement slurry, which is prepared by the following steps:

[0141] Weigh 6 parts of CO2 self-healing agent A, 0.07 parts of defoaming agent and 44 parts of tap water to form a mixed solution and place it in a corrugated can; weigh 46 parts of Jiahua G-grade oil well cement, 37 parts of ultrafine fly ash, 17 parts of phosphate aluminate cement, 5 parts of CO2 anti-corrosion agent A, 0.5 parts of fluid loss reducer, 0.3 parts of dispersant and 0.06 parts of retarder and dry mix them into a solid mixture; add the solid mixture into the mixed solution of the corrugated can within 15 seconds at a low speed of 4600r / min, and then continue stirring at a high speed of 14400r / min for 35 seconds to obtain CO2 corrosion-resistant self-healing cement slurry A.

[0142] Example 2

[0143] This embodiment provides a CO2 corrosion resistant self-repairing cement slurry, which is prepared by the following steps:

[0144] Weigh 6 parts of CO2 self-healing agent B, 0.09 parts of defoaming agent and 44 parts of tap water to form a mixed solution and place it in a corrugated can; weigh 62 parts of Jiahua G-grade oil well cement, 30 parts of ultrafine fly ash, 8 parts of phosphate aluminate cement, 10 parts of CO2 anti-corrosion agent A, 0.7 parts of fluid loss reducer, 0.5 parts of dispersant and 0.08 parts of retarder and dry mix them into a solid mixture; add the solid mixture into the mixed solution of the corrugated can within 15 seconds at a low speed of 4600r / min, and then continue stirring at a high speed of 14400r / min for 35 seconds to obtain CO2 corrosion-resistant self-healing cement slurry B.

[0145] Comparative Example 1

[0146] This comparative example provides a CO2 corrosion resistant self-repairing cement slurry comparative sample, which is prepared by the following steps:

[0147] Weigh 6 parts of CO2 self-healing agent comparison sample C, 0.07 parts of defoaming agent and 44 parts of tap water to form a mixed solution and place it in a corrugated can; weigh 46 parts of Jiahua G-grade oil well cement, 37 parts of ultrafine fly ash, 17 parts of phosphate aluminate cement, 5 parts of CO2 corrosion inhibitor A, 0.5 parts of fluid loss reducer, 0.3 parts of dispersant and 0.06 parts of retarder and dry mix them into a solid phase mixture; add the solid phase mixture into the mixed solution of the corrugated can within 15 seconds at a low speed of 4600r / min, and then continue stirring at a high speed of 14400r / min for 35 seconds to obtain the CO2 corrosion-resistant self-healing cement slurry comparison sample C.

[0148] Comparative Example 2

[0149] This comparative example provides a CO2 corrosion resistant self-repairing cement slurry comparative sample, which is prepared by the following steps:

[0150] Weigh 6 parts of CO2 self-healing agent B, 0.07 parts of defoaming agent and 44 parts of tap water to form a mixed solution and place it in a corrugated can; weigh 46 parts of Jiahua G-grade oil well cement, 37 parts of ultrafine fly ash, 17 parts of phosphate aluminate cement, 0.5 parts of fluid loss reducer, 0.3 parts of dispersant and 0.06 parts of retarder and dry mix them into a solid mixture; add the solid mixture into the mixed solution of the corrugated can within 15 seconds at a low speed of 4600r / min, and then continue stirring at a high speed of 14400r / min for 35 seconds to obtain the CO2 corrosion resistant self-healing cement slurry comparison sample D.

[0151] Example 3

[0152] This embodiment provides a CO2 corrosion resistant cement slurry, which is prepared by the following steps:

[0153] Weigh 0.09 parts of defoamer and 44 parts of tap water to form a mixed solution and place it in a corrugated can; weigh 100 parts of Jiahua G-grade oil well cement, 10 parts of CO2 corrosion inhibitor A, 0.7 parts of fluid loss reducer, 0.2 parts of dispersant and 0.08 parts of retarder and dry mix them into a solid mixture; add the solid mixture into the mixed solution in the corrugated can within 15 seconds at a low speed of 4600 r / min, and then continue stirring at a high speed of 14400 r / min for 35 seconds to obtain CO2 corrosion-resistant cement slurry E.

[0154] Comparative Example 3

[0155] This embodiment provides a comparative sample of CO2 corrosion resistant cement slurry, which is prepared by the following steps:

[0156] Weigh 0.09 parts of defoamer and 44 parts of tap water to form a mixed solution and place it in a corrugated can; weigh 100 parts of Jiahua G-grade oil well cement, 10 parts of CO2 anti-corrosion agent comparison sample B, 0.7 parts of fluid loss reducer, 0.2 parts of dispersant and 0.08 parts of retarder and dry mix them into a solid mixture; add the solid mixture into the mixed solution in the corrugated can within 15 seconds at a low speed of 4600 r / min, and then continue stirring at a high speed of 14400 r / min for 35 seconds to obtain CO2 corrosion-resistant cement slurry F.

[0157] Test Example 1

[0158] The CO2 corrosion resistant self-repairing cement slurries A, B, C, D and CO2 corrosion resistant cement slurries E and F prepared in Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were placed in a high temperature and high pressure curing kettle. After continuous curing for 90 days at 90°C, total pressure of 35 MPa and CO2 partial pressure of 30 MPa, the compressive strength stability and fracture permeability recovery rate were as shown in Table 1 and tested according to the oil well cement test method GB / T 19139-2012.

[0159] Table 1 Compressive strength stabilizer and permeability recovery of self-repairing cement paste against CO2 corrosion

[0160]

[0161] Note: Blank system formula: G-grade oil well cement + 0.2% dispersant (G408FJ) + 0.44% tap water, density 1.90g / cm 3 .

[0162] The experimental results show that under the conditions of 90℃\total pressure of 35MPa\CO2 partial pressure of 30MPa, after continuous curing for 90 days, the compressive strength decay rates of blank cement paste, cement paste A, cement paste B, cement paste C and cement paste D are 69.41%, 4.35%, 2.16%, 38.46% and 42.19% respectively. Compared with blank cement paste, the compressive strength stability of cement paste A, cement paste B, cement paste C and cement paste D are enhanced by 93.7% and 1.2% respectively. The permeability recovery rates of blank cement paste, cement paste A, cement paste C and cement paste D were 12.14%, 90.05%, 92.17%, 26.93% and 91.86% respectively. Compared with blank cement paste, the permeability recovery rates of cement paste A, cement paste B, cement paste C and cement paste D were enhanced by 77.91%, 80.03%, 14.79% and 79.72% respectively. The compressive strength decay rates of cement paste E and F were 40.70% and 66.24% respectively. Compared with blank cement paste, the compressive strength stability was enhanced by 41.36% and 4.57% respectively. Therefore, the CO2 corrosion-resistant self-repairing cement slurry for CCUS injection-production well cementing of the present invention can solve the technical problems of cement ring matrix damage caused by acidic medium CO2 corrosion and alternating loads during CO2 injection in the wellbore cementing of the injection-production well in CCUS engineering construction, annular air leakage caused by micro-gaps and micro-cracks in the annulus, and damage to the wellbore integrity.

[0163] Test Example 2

[0164] The comprehensive properties of the CO2 corrosion resistant self-repairing cement slurries A and B and the comparative slurries C and D formed by the present invention are shown in Table 2, and the tests were carried out according to the oil well cement test method GB / T 19139-2012.

[0165] Table 2 Comprehensive performance of CO2 corrosion resistant self-repairing cement slurry

[0166]

[0167] The API water loss of cement slurry A and B systems is 0mL, the API water loss is less than 35mL, which meets the API standard, the fluidity range is 22-23cm, the rheological parameter n value range is 0.90-0.92, and the consistency coefficient K value range is 0.66-0.68. The API water loss of cement slurry C and D systems is 0mL, the API water loss is less than 40mL, which meets the API standard, the fluidity range is 23.5-24.9cm, the rheological parameter n value range is 0.81-0.84, and the consistency coefficient K value range is 0.71-0.73. Therefore, the cement slurry system of the present invention not only has good flow rheological properties, but also has excellent sedimentation stability performance. The cement slurry system has good comprehensive engineering performance and fully meets the basic requirements of on-site cementing construction.

Claims

1. A CO2 anticorrosive agent, which comprises, by weight, 43-47 parts of calcite, 35-38 parts of calcium carbonate whiskers, and 15-22 parts of nano-silicon dioxide.

2. The CO2 anticorrosive agent according to claim 1, wherein The passing rate of the calcite 80-mesh sieve is ≥ 95.0%; Preferably, the calcium carbonate whisker has a diameter of 1-2 μm, a fiber length of 20-30 μm, and an aspect ratio of 20-30; Preferably, the nano-silicon dioxide has a contact angle of 76°-83° and a particle size of 12-25 nm.

3. Use of the CO2 anticorrosive agent according to claim 1 or 2 in oil well cement.

4. A CO2 corrosion resistant self-repairing cement slurry system, which comprises, by weight: 46-62 parts of G-grade oil well cement, 30-37 parts of ultrafine fly ash, 8-17 parts of phosphate aluminate cement, 4-6 parts of CO2 self-repairing agent, 5-10 parts of CO2 corrosion inhibitor, 0.4-0.8 parts of fluid loss reducer, 0.2-0.5 parts of dispersant, 0.05-0.10 parts of retarder, 0.05-0.10 parts of defoamer, and water; the ratio of the mass of the water to the sum of the mass of G-grade oil well cement, ultrafine fly ash, and phosphate aluminate cement is 0.38-1.30:1; Wherein, the CO2 anticorrosion agent is the CO2 anticorrosion agent according to claim 1 or 2; The CO2 self-healing agent has a core-shell structure; the core layer comprises a polymer obtained by polymerization of core layer monomers, and the core layer monomers include formaldehyde-urea prepolymer and crotonic acid; the shell layer comprises a polymer obtained by polymerization of shell layer monomers, and the shell layer monomers include acrylate monomers and cyclohexanolactam.

5. The CO2 corrosion resistant self-repairing cement slurry system according to claim 4, wherein: Calculated based on the mass of the CO2 self-repairing agent as 100%, the composition of the CO2 self-repairing agent includes 30-34% formaldehyde-urea prepolymer, 25-29% crotonic acid, 23-26% acrylate monomer, and 11-22% cyclohexanolactam; Preferably, the acrylic acid ester monomer includes one or a combination of two or more of butyl acrylate, ethyl acrylate, methyl methacrylate, methyl acrylate, and isooctyl acrylate.

6. The CO2 corrosion resistant self-repairing cement slurry system according to claim 4, wherein: The preparation method of the CO2 self-repairing agent comprises the following steps: (1) emulsion polymerization of the core layer monomer to obtain the core layer emulsion of the CO2 self-healing agent; (2) preparing a shell layer on the surface of the core layer of the CO2 self-healing agent by emulsion polymerization of the shell layer monomer to obtain the CO2 self-healing agent; Preferably, step (1) comprises the following steps: (a) mixing the formaldehyde-urea prepolymer, crotonic acid, an emulsifier and water to obtain a core layer monomer solution; (b) treating 25-35 wt % of the obtained core layer monomer solution with an initiator to obtain a core layer seed emulsion; (c) adding the remaining core layer monomer solution and the initiator to the obtained core layer seed emulsion for reaction to obtain the core layer emulsion of the CO2 self-healing agent; Preferably, step (2) comprises the following steps: (d) mixing the acrylic acid ester monomer, cyclohexanolactam, emulsifier and water to obtain a shell monomer solution; (e) preparing a shell layer on the surface of the core layer of the CO2 self-healing agent by using the obtained shell layer monomer solution under the action of an initiator to obtain the CO2 self-healing agent.

7. According to the CO2 corrosion resistant self-repairing cement slurry system of claim 4, the preparation method of the formaldehyde-urea prepolymer comprises the following steps: The raw material composition of the formaldehyde-urea prepolymer includes urea and formaldehyde in a molar ratio of 1:1.1-1:1.4; 35-42% of the total amount of urea raw materials and polyacrylamide are mixed in water, the pH value is adjusted to 7-9 by triethanolamine, and the mixture is reacted at 50-65° C. for 90-120 minutes; 40-50% of the total amount of urea raw materials and formaldehyde solution are then added, the pH value is adjusted to 4-6 by acetic acid, and the mixture is reacted for 120-150 minutes; finally, 8-25% of the total amount of urea raw materials are added, the pH value is adjusted to 4-6 by acetic acid, and the mixture is reacted at 65-70° C. for 120-150 minutes to obtain the formaldehyde-urea prepolymer; Preferably, the amount of polyacrylamide added is 3.5-6.2% of the total amount of urea raw material, and the molecular weight of the polyacrylamide is 3-5 million.

8. The CO2 corrosion resistant self-repairing cement slurry system according to claim 6, wherein in the preparation method of the CO2 self-repairing agent, the mass percentage concentration of the core layer monomer solution is 25-30%; Preferably, in step (a), stirring is performed at 25000 r / min-28000 r / min for 15-20 min to obtain the core layer monomer solution; Preferably, in step (a), the emulsifier comprises a nonionic emulsifier, more preferably a mixture of dodecyl to octadecyl alcohol polyoxyethylene ether and octylphenol polyoxyethylene ether, further preferably a mixture of dodecyl to octadecyl alcohol polyoxyethylene ether and octylphenol polyoxyethylene ether in a mass ratio of 1:3; Preferably, in step (a), the amount of the emulsifier added is 3.2-4.5% of the mass of the core layer monomer; Preferably, in step (b), the amount of initiator added is 0.8-1.2% of the mass of the obtained core layer monomer solution of 25-35wt%; Preferably, in step (c), the amount of initiator added is 0.8-1.2% of the mass of the remaining core layer monomer solution; Preferably, in step (b), the reaction temperature is 55-65°C; Preferably, in step (c), the remaining core layer monomer solution and initiator are added dropwise to the core layer seed emulsion at 65-70° C. for 50-70 min, and the reaction is carried out for 6-8 h; Preferably, in step (b) or step (c), the initiator comprises azobisisobutyronitrile and ammonium persulfate. More preferably, the initiator is added in the form of a composite solution of azobisisobutyronitrile and ammonium persulfate in a mass ratio of 1:1 with a mass concentration of 20-35%.

9. The CO2 corrosion resistant self-repairing cement slurry system according to claim 6, wherein in the preparation method of the CO2 self-repairing agent, the mass percentage concentration of the shell monomer solution is 20-25%; Preferably, in step (d), stirring is performed at 25000 r / min-28000 r / min for 15-20 min to obtain the shell monomer solution; Preferably, in step (e), the amount of initiator added is 0.8-1.0% of the mass of the shell monomer solution; Preferably, in step (e), the shell layer monomer solution and the initiator are added dropwise to the core layer emulsion at 85-90° C. for 120-140 min, and the reaction is continued for 10-12 h; Preferably, in step (d), the emulsifier comprises nonylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate and sodium p-styrene sulfonate, more preferably a mixture of nonylphenol polyoxyethylene ether, sodium dodecylbenzene sulfonate and sodium p-styrene sulfonate in a mass ratio of 2:1:3; Preferably, in step (d), the amount of the emulsifier added is 3.8-4.9% of the mass of the shell monomer; Preferably, in step (e), the initiator comprises azobisisobutyronitrile and ammonium persulfate, and more preferably, the initiator is added in the form of a composite solution of azobisisobutyronitrile and ammonium persulfate in a mass ratio of 1:1 with a mass concentration of 20-25%.

10. The CO2 corrosion resistant self-repairing cement slurry system according to claim 4, wherein: The silicon content of the ultrafine fly ash is ≥96.0%, the silicon ratio value SM is between 1.8-3.2, and the passing rate of the 1345 mesh sieve is ≥95.0%.

11. The method for preparing the CO2 corrosion resistant self-repairing cement slurry system according to any one of claims 4 to 10, comprising the following steps: The CO2 self-repairing agent, defoaming agent and water are mixed to obtain a mixed solution; Class G oil well cement, ultrafine fly ash, phosphate aluminate cement, CO2 anti-corrosion agent, fluid loss reducer, dispersant and retarder are mixed into a solid phase mixture, and then mixed with the obtained mixed solution to obtain the CO2 corrosion resistant self-repairing cement slurry system.

12. Use of the CO2 corrosion resistant self-repairing cement slurry system according to any one of claims 4 to 10 as oil well cement.